Franz von Ottenthal (1818–1899) - Taddei, Elena (Böhlau, 2021)
Dr. Franz von Ottenthal served as a General Practitioner in Sand, in the South Tyrolean Tauferer Ahrntal from 1847 to 1899, over a period lasting more than 50 years. From 1861 until 1882, in a period of great regional and imperial tensions, he even was member of the Tyrolean Landtag (diet). In 1837/8 he began his medical studies at the University of Vienna, where important physicians from the "Zweite Wiener Medizinische Schule" like Carl von Rokitansky, Joseph Skoda and Philipp Semmelweis were teaching.